Hospice vs. palliative care: Evolution and differences - Aranđelović Branimirka; Milutinović Dragana; Simić Svetlana (Association of Nurses Technicians and Midwives, 2017)
The forerunners of today's hospices existed in ancient and midlle age within the religious institutions in which they are finding a shelter weary pilgrims, travelers, the poor, the sick and the old. Followed by a historical development to 1967 thanks to Dame Cicely Saunders founded the first modern hospice in the UK. The development of the modern hospice movement began intensive development of palliative care in the world. Terms hospice and palliative care are often used interchangeably, they certainly aren't that. Heterogeneous terminology is partially 'guilty' for the different interpretation of palliative care in different countries. Terms, models and services differ from country to country, particularly between Europe and America. Hospice and palliative care both philosophy are aimed at improving the quality of life of seriously ill and their families. They include a holistic and multidisciplinary approach to treatment. The differences relate to the place of service, stage of disease, as well as criteria to be met by the patient.